Hepatoprotective Activity Of Phyllanthus Amarus Seeds Extracts In CCL4 Treated Rats: In Vitro (Global Journal of Medical Research, 2012)
Aim - To study the hepatoprotective activity of Phyllanthus amarus seeds extracts in CCl4 treated rats. Methods - The crushed and dried seeds of Phyllanthus amarus were divided into two parts; one part was extracted successively with petroleum ether, benzene, chloroform and finally with methanol by soxhlet apparatus and concentrated by rotary vacuum. The other part is extracted by cold maceration process for aqueous extraction. The extracts were used for In-vitro and In-vivo studies to analyze the reparative activity of liver injury due to CCl4 in rats. Results - In-vitro models like Reducing power, Superoxide anion scavenging activity, Hydroxyl radical scavenging activity and Nitric oxide radical scavenging activity were carried out with methanolic extract of Phyllanthus amarus seeds for its antioxidant properties. A protective activity could be demonstrated in the CCl4 induced liver damage in rats. In-vivo methanolic and aqueous extracts of the seeds of Phyllanthus amarus 250mg/kg were found to have protective properties in rats with CCl4 induced liver damage as judged from serum biochemical enzyme marker activities and histopathological studies..
Keywords: Hepatoprotective activity; Phyllanthus amarus seeds; CCl4 and Methanolic extract